Cost-effectiveness comparison between pituitary down-regulation with a gonadotropin-releasing hormone agonist short regimen on alternate days and an antagonist protocol for assisted fertilization treatments - Maldonado, Luiz Guilherme Louzada [UNESP]; Franco Junior, Jose Gonçalves [UNESP]; Setti, Amanda Souza; Iaconelli Jr., Assumpto; Borges Jr., Edson (Elsevier, 2013)
Objective: To compare cost-effectiveness between pituitary down-regulation with a GnRH agonist (GnRHa) short regimen on alternate days and GnRH antagonist (GnRHant) multidose protocol on in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) outcome. Design: Prospective, randomized. Setting: A private center. Patient(s): Patients were randomized into GnRHa (n = 48) and GnRHant (n = 48) groups. Intervention(s): GnRHa stimulation protocol: administration of triptorelin on alternate days starting on the first day of the cycle, recombinant FSH (rFSH), and recombinant hCG (rhCG) microdose. GnRHant protocol: administration of a daily dose of rFSH, cetrorelix, and rhCG microdose. Main Outcome Measure(s): ICSI outcomes and treatment costs. Result(s): A significantly lower number of patients underwent embryo transfer in the GnRHa group. Clinical pregnancy rate was significantly lower and miscarriage rate was significantly higher in the GnRHa group. It was observed a significant lower cost per cycle in the GnRHa group compared with the GnRHant group ($5,327.80 ± 387.30 vs. $5,900.40 ± 472.50). However, mean cost per pregnancy in the GnRHa was higher than in the GnRHant group ($19,671.80 ± 1,430.00 vs. $11,328.70 ± 907.20). Conclusion(s): Although the short controlled ovarian stimulation protocol with GnRHa on alternate days, rFSH, and rhCG microdose may lower the cost of an individual IVF cycle, it requires more cycles to achieve pregnancy. Clinical Trial Registration Number: NCT01468441. © 2013 by American Society for Reproductive Medicine.
Keywords: Controlled ovarian stimulation; GnRHa; GnRHant ICSI; pituitary down-regulation; cetrorelix; recombinant chorionic gonadotropin; recombinant follitropin; triptorelin; adult; controlled study; cost effectiveness analysis; down regulation; drug dose reduction; embryo transfer; female; fertilization in vitro; human; human cell; intracytoplasmic sperm injection; major clinical study; male; oocyte; outcome assessment; pregnancy rate; priority journal; prospective study; randomized controlled trial; spontaneous abortion; Adult; Cost-Benefit Analysis; Down-Regulation; Drug Administration Schedule; Embryo Transfer; Female; Fertilization in Vitro; Follicle Stimulating Hormone; Follow-Up Studies; Gonadotropin-Releasing Hormone; Humans; Pituitary Gland; Pregnancy; Prospective Studies; Recombinant Proteins; Treatment Outcome; Triptorelin Pamoate